Fault detection for hybrid-triggered networked systems subject to delay and deception attacks - Dai, Shifang; Hai, Lin; Liu, Jinliang; Tian, Engang (Journal of the Franklin Institute, 2025)
This article investigates the fault detection problem for hybrid-triggered networked systems subject to delay and deception attacks. A hybrid-triggered scheme is exploited to balance network bandwidth and system performance. Firstly, the fault detection framework is constructed and modeled in the hybrid-triggered networked system, in which a plant system with faults occurring randomly and a fault detection filter (FDF) system are formulated. Based on the framework, the sufficient conditions for our FDF system to achieve H∞ performance stability are proved by Lyapunov stability theory and described by several matrix inequalities. Meanwhile, the desired matrices of our FDF are also determined by solving a set of linear matrix inequalities (LMIs), which is the primary purpose of this work. In the end, the usefulness of our scheme is validated by simulations.